A Stress-Strain Model for Brick Prism under Uniaxial Compression - Keun-Hyeok Yang; Yongjei Lee; Yong-Ha Hwang (Advances in Civil Engineering)
This study proposes a simple and rational stress-strain relationship model applicable to brick masonry under compression. The brick prism compression tests were conducted with different mortar strengths and with constant brick strength. From the observation of the test results, shape of the stress-strain curve is assumed to be parabola. In developing the stress-strain model, the modulus of elasticity, the strain at peak stress, and the strain at 50% of the peak stress on the descending branch were formulated from regression analysis using test data. Numerical and statistical analyses were then performed to derive equations for the key parameter to determine the slopes at the ascending and descending branches of the stress-strain curve shape. The reliability of the proposed model was examined by comparisons with actual stress-strain curves obtained from the tests and the existing model. The proposed model in this study turned out to be more accurate and easier to handle than previous models so that it is expected to contribute towards the mathematical simplicity of analytical modeling.